Moltmann in America: Impact and Critical Reception - Lösel, Steffen (Theology today, 2024)
The world of Christian theology mourns the passing of Jürgen Moltmann (1926–2024), one of the most prominent Protestant theologians of the twentieth century. Moltmann's death invites a first, albeit only cursory, review of his impact in the US. Since his first stay at Duke University in 1967–1968, he spent much time here, whether on lecture tours, conferences, or for visiting appointments.